2022
DOI: 10.1016/j.resuscitation.2021.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of hyperoxia and factors associated with cerebral oxygenation during cardiopulmonary resuscitation

Abstract: Background: High oxygen levels may worsen cardiac arrest reperfusion injury. We determined the incidence of hyperoxia during and immediately after successful cardiopulmonary resuscitation and identified factors associated with intra-arrest cerebral oxygenation measured with near-infrared spectroscopy (NIRS).Methods: A prospective observational study of out-of-hospital cardiac arrest patients treated by a physician-staed helicopter unit. Collected data included intra-arrest brain regional oxygen saturation (rSO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…To the Editor, We thank Sanfilippo and colleagues for their interest and viewpoints on our recent study assessing the prevalence of hyperoxia and factors associated with cerebral oxygenation during cardiopulmonary resuscitation (CPR). 1 We agree that the prevalence of hyperoxia was lower in our study sample than reported in some previous studies. [2][3][4] Sanfilippo and colleagues suggest that this could be related to the use of near infrared spectroscopy (NIRS) as a part of the study protocol.…”
supporting
confidence: 88%
“…To the Editor, We thank Sanfilippo and colleagues for their interest and viewpoints on our recent study assessing the prevalence of hyperoxia and factors associated with cerebral oxygenation during cardiopulmonary resuscitation (CPR). 1 We agree that the prevalence of hyperoxia was lower in our study sample than reported in some previous studies. [2][3][4] Sanfilippo and colleagues suggest that this could be related to the use of near infrared spectroscopy (NIRS) as a part of the study protocol.…”
supporting
confidence: 88%
“…Following cardiac arrest, the cerebral tissue oxygen tension (PbtO 2 ) drops within minutes to almost zero [ 32 , 33 ]. By administration of a high fraction of inspired oxygen (FiO 2 ) during CPR, the PbtO 2 during optimal experimental conditions, can be restored close to pre-arrest levels [ 32 34 ]. Furthermore, observational studies have demonstrated an association between higher PaO 2 during CPR and greater probability to obtain ROSC [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…During cardiopulmonary resuscitation, before the return of spontaneous circulation, it is conventional to ventilate the lungs with 100% oxygen. In 1 observational study, arterial blood gas analysis during OHCA demonstrated mild hyperoxia in just 1 of 40 patients before ROSC and in 4 of 20 patients immediately after ROSC 8…”
Section: Current Evidencementioning
confidence: 94%
“…In 1 observational study, arterial blood gas analysis during OHCA demonstrated mild hyperoxia in just 1 of 40 patients before ROSC and in 4 of 20 patients immediately after ROSC. 8 In the EXACT (Reduction of Oxygen After Cardiac Arrest) trial, 428 unconscious OHCA patients were randomized by paramedics to an intervention arm with target blood oxygen saturation of 90% to 94% or standard care of 98-100%. 9 In the intervention group, 38.3% survived to hospital discharge (the primary outcome) compared with 47.9% in the standard care group (difference, −9.6%; 95% confidence interval (CI), −18.9% to −0.2%; odds ratio (OR), 0.68; 95% CI, 0.46 to 1.00; P = 0.05).…”
Section: Controlled Oxygenationmentioning
confidence: 99%